Pengembangan Sumber Daya Manusia Melalui Pendidikan Non Formal dan In Formal di Kabupaten Tuban - M Thoyyib (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
In development, humans are planners, actors, controllers and the goal of development itself. Therefore, the development of the quality of human resources is a top priority that must be improved, so that they can have all the capabilities needed in development in all fields. Quality human beings can take advantage of all their potential and be able to seize future opportunities for the glory of the nation and state. The human factor is the most decisive for the success or failure of a nation to remain upright in global competition because what distinguishes the ability of a nation from other nations is its human quality. The central point that is the key to the success or failure of a nation in building its country, depends on the quality of its human resources. The author argues, Islam, especially in Indonesia, can emerge with strong and quality Muslims if it has three factors that have been fulfilled, namely